Show me the money: Option moneyness concentration and future stock returns. Issue 5 (7th November 2019) - Bergsma, Kelley; Csapi, Vivien; Diavatopoulos, Dean; Fodor, Andy
Abstract: Informed traders often use options that are not in‐the‐money due to higher potential gains for a smaller upfront cost. Thus, trading activity by option moneyness should be a gauge of informed option trading. We construct a dollar volume‐weighted average moneyness measure to capture option trading activity at different moneyness levels. Stock returns increase with this measure, suggesting more trading activity in options with higher leverage predicts future stock returns. Our results hold cross‐sectionally and at the portfolio level yielding a Fama–French five‐factor α of 12% per year for all stocks and 33% per year for high implied volatility stocks.